Peran Posyandu dalam Mendukung Program Kesehatan Anak di Dusun 3 Desa Sei Glugur - Rani Ramadani; Imelita Rahyuni Ritonga; Dessy Nurfiani; Ainun Jawahir; An'nas Tasya Ramadhani; Rani Suraya (Lembaga Pengembangan Kinerja Dosen, 2025)
the role of Posyandu (Integrated Service Post) in Hamlet III Sei Glugur Village in supporting community health programs, especially for mothers and children. Posyandu provides various activities such as immunizations, health education, and monitoring children's growth and development, which facilitates community access to basic health services. Even though there is enthusiasm and positive benefits felt by the community, especially young mothers, the main challenge faced is the lack of public awareness. This research recommends improving facilities, cadre training, and support from the government and community to increase Posyandu participation and effectiveness.